Psychotherapists' perceptions of countertransference in working with psychotic patients. - Cain, Wendy (My University, 2011)
In literature as well as published case material, psychotherapists are often reported to experience a range of strong countertransferential reactions in working with psychotic patients. In this study, psychotherapists’ experiences of countertransference in their work with psychotic patients were examined, and how these responses are perceived to impact on therapy was also investigated. Non-probability, convenience sampling was used. The sample consisted of seven participants, one male and six female psychotherapists working in the Johannesburg vicinity. Semi-structured interviews were used, and the data was analysed using thematic content analysis. The results of this analysis have shown that the participants in their work with psychotic patients experienced various, multi-levelled countertransference responses. Firstly, the results indicate that participants report experiencing feelings such as fear; horror; anxiety; frustration; anger; sadness and disintegration. Secondly, the participants described the quality or characteristics of the feelings themselves (termed ‘meta-affective’ themes), these relating to either the reported intensity of feelings, or views on who is ‘causing’ the feelings in therapy. The final level to these countertransferential experiences described aspects of the relationship between patient and therapist and how the countertransferential feelings are involved in this, these included themes of power, responsibility, avoidance and boundaries. Discussion drew on psychoanalytic theory in understanding the intersection of these countertransferential feelings with the particular presentation evidenced in psychosis. To the author’s knowledge, there is no research previously conducted in South Africa addressing this aspect of therapeutic contact with psychotic patients, as such some recommendations suggested for future research were made. These include: further exploration of therapeutic contact with psychotic patients in South Africa – including the exploration of other professionals’ countertransference experiences such as those experienced by psychiatric nursing staff, furthermore it is recommended that research be done in regards to exploring countertransferential reactions in brief-term work with this patient population.